Optimalisasi Peran Koperasi Wanita Dalam Meningkatkan Kesejahteraan Anggota (Studi pada Koperasi Wanita Potre Koneng Kabupaten Sumenep) - Deasy Dwi Ratnasari (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2013)
Abstract: Optimization the Role of Women in Improving Welfare Cooperative Members. Related many Women's Cooperative in East Java, especially Sumenep, Women's Cooperative in 2011 Potre Koneng members reach 1,158 people. Women's Cooperative existence is not optimal because it does not include all residents in the District City Sumenep women, there is no regeneration of the chairman of the cooperative and the store only to members. The purpose of writing is decrypt and analyze the impact of the optimization efforts and the role of Women's Cooperative Potre Koneng. This research uses descriptive qualitative research method using a model of interactive data analysis Spradley. Role in the optimization of the Women's Cooperative Potre Koneng existing efforts through capacity development (capacity building) include human resource development, organizational strengthening, institutional reform, participation of members and business diversification. Optimization the impact of the role that the number and activity of members, business development, of net income (SHU) and the surrounding environment. In this case, it still remains on the development of members through training/case study and the business environment as well as to shop in addition to members of the public. Keywords: Women's Cooperative Potre Koneng, Roles, Optimization and Capacity Building Abstrak: Optimalisasi Peran Koperasi Wanita dalam Meningkatkan Kesejahteraan Anggota. Terkait banyaknya Koperasi Wanita di Jawa Timur khususnya Kabupaten Sumenep, Koperasi Wanita Potre Koneng tahun 2011 anggotanya mencapai 1.158 orang. Keberadaan Koperasi Wanita ini belum optimal karena belum mencakup semua penduduk perempuan di Kecamatan Kota Sumenep, tidak ada regenerasi ketua koperasi dan toko hanya untuk anggota. Tujuan penulisan yaitu mendekripsikan dan menganalisis upaya dan dampak optimalisasi peran Koperasi Wanita Potre Koneng. Penelitian ini menggunakan metode penelitian deskriptif kualitatif dengan menggunakan model analisis data interaktif Spradley. Dalam optimalisasi peran Koperasi Wanita Potre Koneng ini sudah ada upaya melalui pengembangan kapasitas (capacity building) meliputi pengembangan sumber daya manusia, penguatan organisasi, reformasi kelembagaan, partisipasi anggota dan diversifikasi usaha. Dampak optimalisasi peran yaitu jumlah dan aktivitas anggota, pengembangan usaha, sisa hasil usaha (SHU) dan lingkungan sekitar. Dalam hal ini masih perlu ditekankan pada pengembangan anggota melalui diklat/studi banding dan lingkungan yaitu usaha toko selain anggota juga untuk umum. Kata Kunci: Koperasi Wanita Potre Koneng, Peran, Optimalisasi dan Capacity Building